Does Firm Growth Strengthen the Effect of Profitability and Liquidity on Firm Value? Empirical Evidence from Consumer Non-Cyclicals Firms in Indonesia - Natasya Aprilia Karren Wilson; Hais Dama; Mohamad Agus Salim Monoarfa (Transbahasa, 2026)
This study aims to analyze the effect of profitability and liquidity on firm value, with firm growth serving as a moderating variable, in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The study employed a quantitative research approach using secondary data obtained from the annual financial reports of listed companies. A purposive sampling technique was applied to select companies that met the predetermined criteria, resulting in a final sample of 52 companies with a total of 156 observations over the three-year period. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach with SmartPLS version 3.2.9. The findings reveal that profitability has a positive and significant effect on firm value, indicating that companies with higher profitability tend to achieve higher market valuations. Conversely, liquidity has a negative and significant effect on firm value, suggesting that excessive liquidity may be perceived as inefficient asset utilization by investors. Furthermore, firm growth does not have a significant effect on firm value. The moderation analysis also demonstrates that firm growth is unable to strengthen or weaken the relationship between profitability and firm value, as well as between liquidity and firm value. These findings provide empirical evidence regarding the determinants of firm value and contribute to the financial management literature by highlighting the limited moderating role of firm growth in consumer non-cyclicals companies.